Stochastic dynamics of Musca domestica (Diptera: Muscidae) and Chrysomya putoria (Diptera: Calliphoridae) - Cerigatto, Wanderley [UNESP]; Souza Riback, Thais Irene; Thyssen, Patricia Jacqueline [UNESP]; Reigada, Carolina [UNESP]; Moretti, Thiago de Carvalho [UNESP]; Conde Godoy, Wesley Augusto [UNESP] (Medwell Online, 2009)
We analysed the stochastic dynamics of Musca domestica L. (Muscidae) and Chrysomya putoria (Wiedemann) (Calliphoridae), 2 important dipteran species that are pests of poultry housing. The study, is an attempt to examine demographic attributes of each species and compare ecological patterns of fluctuation, by combining empiricism with ecological modelling. The results of the ecological simulations suggest differences between the 2 species with respect to susceptibility to local extinction. Musca domestica is a species with a better population performance than that of C. putoria, mainly with respect to its survival. Chrysomya putoria is apparently more prone to extinction than is M. domestica and with stochastic fecundity exhibited fluctuations trending to cyclic oscillations, differing clearly from M. domestica. A reverse result was observed in M. domestica. With stochastic survival it was more prone to exhibit cycling than was C. putoria These results are important to the implementation of population-control programs, mainly emphasising the implications of biological invasions and colonisation of new areas by exotic species.
Keywords: Stochastic dynamics; Musca domestica; Chrysomya putoria; demographics